Learning from Mickey, Donald and Walt essays on Disney's edutainment films - Van Riper, A. Bowdoin (McFarland & Co., 2011)
"Throughout its long and colorful history, Walt Disney Studios has produced scores of films designed to educate moviegoers as well as entertain them. Each of the essays in this volume focuses on a different type of Disney "edutainment" film. Together they provide the first comprehensive look at Walt Disney's ongoing mission to inform and enlighten his worldwide audience"--Provided by publisher.